Nurses’ knowledge, attitude, and practice of low-flow oxygen therapy and humidification - Tang, Naiwang; Li, Haiying; Zhang, Jiayi; Ling, Hua; Shi, Linlin; Zhang, Huili; Guo, Qi; Yu, Ronghuan (Frontiers in Medicine, 2024)
Objective Nurses are key in administering oxygen therapy and managing its potential adverse effects in medical settings. This study aimed to investigate the knowledge, attitudes, and practices (KAP) regarding low-flow oxygen therapy and humidification among nurses. Methods This cross-sectional study was conducted from January 2024 to March 2024 at Shanghai Xuhui Central Hospital. Demographic data and KAP scores were collected through questionnaires. Result A total of 243 valid questionnaires were collected. Among them, 228 (93.8%) were female, and 93 (38.3%) had been working for more than 10 years. The mean scores for knowledge, attitudes, and practices were 11.11 ± 4.30 (Ranging 0–18), 29.14 ± 3.41 (Ranging 7–35), and 28.07 ± 4.73 (Ranging 7–35), respectively. Multivariate logistic regression confirmed that knowledge (OR = 1.302, 95% CI: [1.167–1.453], p < 0.001) and attitudes (OR = 1.196, 95% CI: [1.080–1.325], p < 0.001) were independently associated with proactive practices. Structural equation modeling (SEM) corroborated the direct influences of training (β = 3.210, p < 0.001) and clinical experience (β = 2.044, p = 0.002) on knowledge, with knowledge (β = 0.379, p < 0.001) and gender (β = −1.642, p = 0.037) directly impacting attitudes. Additionally, knowledge (β = 0.395, p < 0.001), attitudes (β = 0.340, p < 0.001), and equipment utilization (β = 1.098, p < 0.001) directly influenced practices. Conclusion Nurses demonstrated inadequate knowledge, positive attitudes, and inactive practices toward low-flow oxygen therapy and humidification. Enhanced training and increased clinical experience are recommended to improve nurses’ knowledge and practice in this area.